A next-generation wide color gamut WLED with improved spectral performance in phosphor composite functional solid. Issue 17 (1st December 2020) - Dou, Benle; Du, Wenbo; Huang, Feifei; Ma, Hongping; Hua, Youjie; Zhang, Junjie; Xu, Shiqing
Abstract: As is well known, a way to obtain a high color resolution and saturation of a liquid crystal display and thereby obtain a higher visual accuracy and comfort in the coming 5G era remains an urgent challenge. In the present study, a new type of phosphor composite material doped with Ln 3+ ions provides a promising alternative to the color filters used in White light-emitting diodes (WLEDs), achieving a better performance regarding the realization of a wider color gamut. The advantages of this composite material are illustrated through an abundant phase and morphology analysis along with a discussion regarding the X-ray photoelectron spectroscopy of the valence bond of Ce ions, which maintain the luminescence properties of the phosphor while providing a stable and solid amorphous environment. An improved spectral performance was obtained through color filtering at 580 nm along with the regulating effects of red, green, and blue emissions according to the doped Ln 3+ ions. Notably, we fabricated a high-performance WLED based on a Ln 3+ -doped PiG with a correlated color temperature of 5037 K, color rendering index of 72.8, and high color gamut of 91.97%, providing a new choice for the development of luminescence materials with a high color resolution and saturation.